Inkonsistensi Paradigma Otonomi Daerah di Indonesia: Dilema Sentralisasi atau Desentralisasi - Wasisto Raharjo Jati (The Constitutional Court of the Republic of Indonesia, 2012)
This study aimed to analyze trajectory of regional autonomy in Indonesia. There are two important things in discussing about regional autonomy in Indonesia. Firstly, dilemma between decentralization or centralization as basic paradigm in the policy of regional autonomy. Secondly, regional autonomy just creates oligarchy regime, primordialism, and politic of clientelism. Implementation of regional autonomy has been became new problems for Indonesia which adopted unitary state system. Regional autonomy in post New-Order era intended to enhancing participation of society in development project and local democracy was hijacked by many interest from elite. In other words, regional autonomy more aligned to elite rather than the people.